2007
DOI: 10.1007/s11295-007-0108-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural phenological variation in aspen (Populus tremula): the SwAsp collection

Abstract: The genus Populus is currently the main model system for genetic, genomic, and physiological research in trees. Phenotypic variation in aspen (Populus tremula) populations growing in different environments across Sweden is expected to reflect genetic variation that is important for local adaptation. To analyze such natural phenotypic and genetic variation, the Swedish Aspen (SwAsp) Collection was established. Trees were taken from 12 different populations across Sweden, from 56°to 66°l atitude north and plante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(209 citation statements)
references
References 42 publications
8
200
1
Order By: Relevance
“…Lastly, the F ST values of SNPs did not deviate significantly from neutral expectations based on the Bayesian F ST test. Our results are in line with recent data obtained in various species, in which differentiation of CGs was compared with differentiation of neutral markers and of the target trait (Eveno et al (2008) in P. pinaster; Pyhäjärvi et al (2008) in P. sylvestris; Heuertz et al (2006) in Picea abies; Hall et al (2007) and Luquez et al (2007) in P. tremula). In all these case studies, the mean differentiation of genes was of the same level as differentiation of the neutral markers and far less than differentiation of the target trait.…”
Section: Differentiation Of Cgs Versus Trait Differentiationsupporting
confidence: 92%
“…Lastly, the F ST values of SNPs did not deviate significantly from neutral expectations based on the Bayesian F ST test. Our results are in line with recent data obtained in various species, in which differentiation of CGs was compared with differentiation of neutral markers and of the target trait (Eveno et al (2008) in P. pinaster; Pyhäjärvi et al (2008) in P. sylvestris; Heuertz et al (2006) in Picea abies; Hall et al (2007) and Luquez et al (2007) in P. tremula). In all these case studies, the mean differentiation of genes was of the same level as differentiation of the neutral markers and far less than differentiation of the target trait.…”
Section: Differentiation Of Cgs Versus Trait Differentiationsupporting
confidence: 92%
“…Furthermore, this discrepancy increases as the number of loci involved in the trait increases. (Eveno et al, 2008), bud set in P. sylvestris (Pyhäjärvi et al, 2008) and Picea abies (Heuertz et al, 2006), phenological traits (bud burst, length of growing season and leaf abscission) and growth traits (height growth and diameter) in Populus tremula Luquez et al, 2007), bud burst in Quercus petraea (Derory et al, 2010) and growth, phenology and wood characters in Picea glauca (Namroud et al, 2008). In each case, the level of differentiation of the candidate genes was similar to that of neutral markers, whereas Q ST values were much higher.…”
Section: Discussionmentioning
confidence: 93%
“…For example, in forest trees, in which extensive common gardens have been established, known as provenance tests, substantial population differentiation has been observed for almost all phenotypic traits assessed (see Wright (1976) and Morgenstern (1996) for reviews on North American species, and König (2005) for a review on European species). Only a few studies have investigated the differentiation of traits and their underlying genes, and these studies have concluded that there is considerable discrepancy between these two measurements Luquez et al, 2007;Namroud et al, 2008). Theoretical predictions supported by simulations have indeed indicated that there may be large discrepancies between phenotypic differentiation (Q ST ) and differentiation of the genes controlling the trait (G STq , for quantitative loci, as suggested by Santure and Wang (2009), to avoid confusion with neutral G ST or F ST ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both genes appear to have a multifunctional role, which may contribute to the maintenance of a larger diversity due to balancing selection in natural conditions. Hall et al, 2007;Luquez et al, 2007). In all these case studies, the mean differentiation of genes was of the same level than that of the neutral markers and far less than differentiation of the target trait.…”
Section: Diversity Of Cgs Of Bud Burst Vs Diversity Of Neutral Markersmentioning
confidence: 83%